PENGEMBANGAN BAHAN AJAR ARITMATIKA SOSIAL UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA SMP - Pujia Siti Balkist; Hamidah Suryani Lukman; Nita Andriani (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2022)
This study aims to determine the validity of animation-based teaching material of social arithmetic topic animation-based teaching material of social arithmetic to improve students' understanding of mathematical concepts. The method used in this research is R&D research with Borg and Gall development model which is limited to 5 stages, namely potential and problems, finding information, product design, design validation, and design improvement. By involving 3 experts namely 2 material experts and 1 media expert. The results of the study show that animation-based teaching material of social arithmetic are very valid with an average percentage of material experts at 93.5% and 96% of media experts.